Prevalence and influencing factors of comorbidity of central obesity and hyperuricemia in adult residents of Inner Mongolia Autonomous Region in 2018: a cross-sectional survey - Lehui LI; Xingguang ZHANG; Nan ZHANG; Tao YAN; Yonggang QIAN; Huimin LIU (Zhongguo gonggong weisheng, 2025)
ObjectiveTo investigate the prevalence and influencing factors of the comorbidity of central obesity and hyperuricemia (HUA) among adult residents in the Inner Mongolia Autonomous Region, and to provide evidence for developing prevention and control strategies. MethodsA cross-sectional study was conducted among 5 076 permanent residents aged ≥18 years in the Inner Mongolia Autonomous Region from July to December 2018. Participants were recruited using stratified multistage cluster sampling across 8 districts, banners, counties, and cities, stratified by population size and geographic location to ensure a representative sample. Data were collected via questionnaires, physical examinations, and serum uric acid tests. The prevalence of comorbid central obesity and HUA was calculated as the proportion of participants diagnosed with both conditions. An unconditional multivariate logistic regression model was used to identify the main influencing factors of this comorbidity. ResultsOf the 4731 participants finally included in the analysis, 2 139 (45.2%), 520 (11.0%), and 296 (6.3%) were identified as with central obesity, HUA, and comorbid central obesity and HUA, respectively. Multivariable unconditional logistic regression analysis showed that having sleep problems was a risk factor of comorbid central obesity and HUA, while being female, aged ≥ 40 years, and having rural household registration were protective factors against the comorbidity. ConclusionsAlthough the prevalence rate of central obesity with HUA among adult residents in the Inner Mongolia Autonomous Region is relatively low, it still warrants attention. Gender, age, type of registered residence, and sleep problems are identified as the primary influencing factors for central obesity with HUA among local adult residents.